Assessing Two Dimensions of Interpersonal Trust: Other-Focused Trust and Propensity to Trust - Zhang, Ming (Frontiers in Psychology, 2021)
One’s propensity to trust others and others’ trustworthiness are two important aspects of interpersonal trust. Both theory and research suggest that it is possible to distinguish between an individual’s propensity to trust (one’s ‘trustingness’ or the extent to which one feels able to trust others) and their other-focused trust (the extent to which one feels that others are worthy of our trust). However, there is as yet no measure that distinguishes between these two components of trust. In three studies, we examined the psychometrics of a proposed two- dimensional measure of trust that encompasses propensity to trust and other-focused trust components. To test discriminant validity, we also administered measures of personality, personal self-esteem, social capital, propensity to like people, perceived social support, as well as general and personal beliefs in a just world. Factor analyses supported the proposed two-factor model for the new trust measure. Further analyses supported the difference between these measures.